2009
DOI: 10.3168/jds.2008-1252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lipid supplementation on the yield and composition of milk from cows with different β-lactoglobulin phenotypes

Abstract: Responses to lipid supplementation differ between dairy breeds and genetic lines suggesting nutrition by genotype interactions. beta-Lactoglobulin phenotype is associated with changes in yield and composition of milk. The response of cows with different beta-lactoglobulin phenotypes to lipid supplementation has not been examined. Furthermore, we examined whether lipid supplementation alters milk protein composition. By using a randomized block design, we fed Holstein cows for 3 wk either a control diet contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
4
5
0
1
Order By: Relevance
“…Variation in results from a few pasture-based systems has also been observed (Kay et al 2007;Hutchinson et al 2011). The findings in this current study agree with previous authors who reported an increase in milk yield (Khorasani et al 1991;Chilliard et al 2001;Bobe et al 2009;Hutchinson et al 2012), but contrasts with others who reported either a decrease or no effect on milk production (Bayourthe et al 2000;Chichlowski et al 2005;Bernal-Santos et al 2010;Caroprese et al 2010;He & Armentano 2011). Our finding in this study also concurs with the assertion of increased milk production in cows supplemented with DCCO.…”
Section: Discussionsupporting
confidence: 91%
“…Variation in results from a few pasture-based systems has also been observed (Kay et al 2007;Hutchinson et al 2011). The findings in this current study agree with previous authors who reported an increase in milk yield (Khorasani et al 1991;Chilliard et al 2001;Bobe et al 2009;Hutchinson et al 2012), but contrasts with others who reported either a decrease or no effect on milk production (Bayourthe et al 2000;Chichlowski et al 2005;Bernal-Santos et al 2010;Caroprese et al 2010;He & Armentano 2011). Our finding in this study also concurs with the assertion of increased milk production in cows supplemented with DCCO.…”
Section: Discussionsupporting
confidence: 91%
“…Experimental cows were in the late lactation stage, therefore, characterized by higher concentration of milk protein. Positive influence of fatty supplements on protein content was also confirmed by Bobe et al (2009) experiment. However, Flowers et al (2008 found that supplementation of cow diet with flax seeds (0.17, 0.34 and 0.51 kg/day) does not influence the performance and content of basic components in the milk protein.…”
Section: Discussionsupporting
confidence: 53%
“…With the development of the dairy industry, increasing attention has been devoted to the potential role of epigenetic mechanisms in the regulation of mammary function in dairy cows. Epigenetic initiator signals can influence milk synthesis in genetically selected animals and can alter the expected lactation performance of an animal (Bobe et al, ). DNA methylation, as a key epigenetic signature, is involved in regulating TG biosynthesis (Ehara et al, ).…”
Section: Discussionmentioning
confidence: 99%